PSYCHOLOGICAL AND PHYSIOLOGICAL NATURE OF AUDITORY-RECEPTIVE SKILL - Mirsalixova Robiya (Journal of new century innovations, 2024)
Abstract: The article is intended to profoundly discuss the psychological and physiological nature of auditory-receptive skill, usually known for all as “listening”. This skill implies much more complex approach and attention than it is thought, and incorporate the utilization of other skills and aspects of language. Additionally, difficulties arising in listening and methods to improving it are provided within the article.